Precancerous skin lesions and malignant skin tumors associated with hydroxyurea treatment: Evaluation of a large series and review of the literature - Can Baykal; Kübra Nursel Bölük; Sıla Kılıç Sayar; Şule Öztürk Sarı; Amid Mahmudov; Nesimi Büyükbabani (Galenos Publishing House, 2022)
Background and Design: Malignant skin tumors have been reported in patients using hydroxyurea (HU) for hematological disorders. This study aimed to investigate the characteristics of precancerous skin lesions and malignant skin tumors in association with long-term HU therapy. Materials and Methods: Records of consecutive patients diagnosed with precancerous and cancerous skin lesions during HU therapy in a single dermatology department between 2008 and 2021 were retrospectively analyzed. Results: Among 13 patients (mean age: 66.5 years) treated with HU for five different hematological diseases, 11 had used HU >5 years, whereas the time was shorter in the other two patients. The period between HU treatment initiation and the appearance of the first lesion was approximately 9-10 years. Actinic keratosis (AKs) were found in two patients, non-melanoma skin cancers (NMSCs) accompanied by AKs in seven patients, and only NMSCs in four patients. Melanoma was seen in a patient with NMSCs and AKs. In total, 12 basal cell carcinomas (BCCs), 12 squamous cell carcinomas (SCCs), and one melanoma were diagnosed. The superficial type was the most common type of BCCs, followed by the nodular type. NMSCs were located mainly on the face, followed by the scalp, neck, and extensor surfaces of the upper extremities. Conclusion: The results of this large series support the possibility of the relationship between UV-induced skin cancer and HU therapy. SCCs and BCCs showed equal incidence in the present study in contrast to some previous reports, and different BCC types may occur in these patients. As many patients have more than one malignant skin tumor, protective measures against sunlight, which is another inducing factor for these tumors, and a long-term follow-up, should not be ignored.